Italo Calvino, l’occhio che scrive. La dinamica dell’immagine autoriale di Calvino nella critica italiana - Baldi, Elio (Incontri. Rivista europea di studi italiani, 2015)
Italo Calvino, the eye that writesThe dynamics of Calvino’s authorial image in literary criticismItalo Calvino has been quickly canonized in Italian literary criticism. Already during the lifetime of the Ligurian author a sort of ‘essential Calvino’ has affirmed itself in criticism. This essential Calvino is constituted by a conglomeration of images, ideas and keywords that define the author, at least according to critical consensus. This ‘essential Calvino’ has, however, not only been formed by critics, but certainly too by Calvino himself, who has contributed greatly to his own authorial image. By adopting various roles, from writer to essayist, editor, journalist and director of book series, Calvino managed to influence the reception of his works with a multifaceted authority. The aim of this article is to investigate how Calvino has become ‘Calvino’, the author whose critical image seems to have clear outlines. The idea of Calvino as a precise and geometrical observer, light but thoughtful, multiple but coherent, has been elaborated in a dialogue between the various ‘Calvini’ and literary critics. These images of Calvino do not only have direct and visible repercussions, but also more indirect and invisible consequences. In the case of Calvino, his metaphorical (but also biographical) marginality coincides with his place at the margins of volumes (on covers and in introductions) that he acquired early on in his career and that continues until this day. By interlacing a paratextual and discourse analysis with the institutional and cultural context of Calvino’s career, one can hope to gather a better insight into Calvino’s critical reception and the process of critical circulation and reception in general.